Evidence of cytogenetic and histological damage in specimens of Astyanax lacustris (Pisces, Characidae) exposed to the hydrogen cyanide-based herbicide Dormex® - Layon Zafra-Lemos; Vera Lúcia Lopes; Ana Paula de Santi Rampazzo; Maria Raquel Marçal Natali; Luciana Andreia Borin-Carvalho; Ana Luiza Brito Portela-Castro (Acta Scientiarum: Biological Sciences, 2021)
The herbicide Dormex®, a solution of hydrogen cyanamide, is a growth regulator capable of breaking the dormancy of fruit plants, and is commonly applied in agriculture. However, the biological effects of this product on non-target organisms are unknown. The present study investigated the biological response of Astyanax lacustris (Lütken, 1875) specimens exposed to Dormex® using a chromosome aberration test, the mitotic index, and the histological analysis of the gills. Forty specimens of Astyanax lacustris were obtained from a local breeding facility and divided into 10 groups (nine experimental and one control) with four fish in each aquarium (group). The control group was maintained for 24 hours in dechlorinated water while the experimental groups were allocated to one of nine different treatments, with three concentrations of Dormex®, 0.05, 0.1 and 0.5 mL L-1, and exposure for 24, 48 and 72 hours. The fish exposed to Dormex® presented chromosomal aberrations of a number of types, including chromosomal breaks, acentric fragments, decondensation, and gaps at the three Dormex® concentrations, at all exposure times. The mitotic index decreased significantly in comparison with the control group. The histological preparations of the gills revealed alterations such as hyperplasia, and lamellar fusion and edema, whereas in the control group the structure of the gills was preserved. The cytogenetic analysis revealed the genotoxic potential of the herbicide Dormex® and the morphological alterations of the gills demonstrated the sensitivity of the fish, which responded rapidly to the stressor. These findings reinforce the need for special care and restrictions on the use of these herbicides in agricultural areas located near aquatic environments.